Design of biodegradable blends based on PLA and PCL: From morphological, thermal and mechanical studies to shape memory behavior. (October 2016) - Navarro-Baena, Iván; Sessini, Valentina; Dominici, Franco; Torre, Luigi; Kenny, Jose M.; Peponi, Laura
Abstract: Blending commercial homopolymers represents a low cost and an easy scalable process to extend the use of the pristine homopolymers to an industrial level. Actually, the processing of blends by extrusion is the usual solution followed in the industry. However, commonly polymer blends are immiscible, provoking phase separation, which can be in the macro, micro or nano scale, depending on the polymers as well as on the processing conditions, affecting the final properties of the blends. Therefore, this paper aims to study the shape memory behavior in biodegradable blends based on poly(lactic acid) (PLA) and poly(ε-caprolactone) (PCL) in different concentrations. A completely thermal and mechanical characterization of the blends was performed, correlating the results with the observed morphology. In addition, two different biodegradation studies were performed in order to correlate the effect of each homopolymer with the degradation behavior of the biodegradable blends.